If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6w = 2w + -16 Reorder the terms: -6w = -16 + 2w Solving -6w = -16 + 2w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-2w' to each side of the equation. -6w + -2w = -16 + 2w + -2w Combine like terms: -6w + -2w = -8w -8w = -16 + 2w + -2w Combine like terms: 2w + -2w = 0 -8w = -16 + 0 -8w = -16 Divide each side by '-8'. w = 2 Simplifying w = 2
| .5x+1=2x-20 | | -6w+4=2w-12 | | 18x-12=297 | | 2n+8n=30 | | 2.2m+5.26=-2.66 | | 2x+58=72 | | -4-2n+8n=26 | | 4y-3=7y | | 6q=-8-2q | | 5c+12=7c+11.32 | | 5(0)+7y=0 | | t^2+2t-3= | | (2w+1)= | | 5x+7(1)=2 | | 3y-3x+4=0 | | 0.25x=x-300 | | 5x+7(0)=2 | | 5(0)+7y=2 | | 10y+20x=20800 | | 560=4x+y | | 0.25x=x-19 | | 3+6(x-9)=7-4(x-2) | | 12+3w=56 | | (x^2+2x)=6x-3 | | x-1=√5/2 | | x(x+2)=2x+9 | | -2/5x-9=3.6 | | 42/27 | | -x+5=-2-3x | | -9=2n+5 | | 3p+5=-1+5p | | 4d-2=6+2d |